VAMPIRE ACADEMY - Mead, Richelle 550659, author (New York : razor bill, 2007)
Two years after a horrible incident made them run away, vampire princess Lissa and her guardian-in-training Rose are found and returned to St. Vladimir's Academy, where one focuses on mastering magic, the other on physical training, while both try to avoid the perils of gossip, cliques, gruesome pranks, and sinister plots.